2013
DOI: 10.21608/jfds.2013.70993
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality, Physicochemical and Microbiological Properties of Camel Milk in North Sinai Governorate

Abstract: This study was aimed to evaluate the nutritional quality and compare the general physic-chemical characteristics and microbial properties of camel milk in North Sinai Governorate. The samples were collected from camel grazed on open and close pastures. Also compare the concentration of some elements, amino and fatty acids of the milk samples for both systems. The biological and caloric values were evaluated in both systems. A section of this study was intended to study some technological properties such as coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to Food Agriculture Organization, the value of pH in fresh camel milk is ranged between 6.5-6.7. 16 The pH value recorded in the present study was consistent with those reported in Egypt by several authors [17][18][19][20] with respective values of 6.65, 6.64, 6.6, and 6.6. In contrast, other researchers have reported lower values [21][22][23] (5.43, 5.97, and 5.87), respectively.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…According to Food Agriculture Organization, the value of pH in fresh camel milk is ranged between 6.5-6.7. 16 The pH value recorded in the present study was consistent with those reported in Egypt by several authors [17][18][19][20] with respective values of 6.65, 6.64, 6.6, and 6.6. In contrast, other researchers have reported lower values [21][22][23] (5.43, 5.97, and 5.87), respectively.…”
Section: Resultssupporting
confidence: 91%
“…Our findings were nearly similar to those given by El-Ziney MG et al 40 However, several authors have reported lower levels of contamination rate. 20,35,41,42 On the contrary, a high mean count was determined by others. 29,30,33,34,37 On the other side Bassuony IN et al, 32 reported a much higher detection rate of coliforms (85.7%) out of 35 raw camel milk samples from Matrouh Governorate, Egypt.…”
Section: Total Coliform and Enterobacteriaceae Countmentioning
confidence: 86%
See 1 more Smart Citation
“…The important difference between the RM and EM results could be linked to the lack of calibration with camel milk. Indeed, all the published data regarding FPD in camel milk were based on results obtained by EM [6][7][8]20] or even by using a simple thermometer [21], but never with the reference method. Moreover, none of the references regarding camel milk have specified if the used apparatus was calibrated for camel milk.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the determination of freezing point in the camel dairy industry is relatively recent, accompanying the recent development of the camel milk sector in many camel countries [4]. Some references on FPD are available in the literature, but without using the reference method (RM) ISO 5764|IDF 108:2009 [5], and most of the time, limited in the number of samples involved [6,7], or without monitoring of the same animals [8]. Usually, the determination of FPD is included in a battery of physico-chemical analyses not necessarily focused on long-term variation factors [9].…”
Section: Introductionmentioning
confidence: 99%